Understanding Influencing Factors of Students’ Motivation to Learn English: A Case Study at SMAN 1 Batukliang Utara - Pebriani Rahmania; Henny Soepriyanti; Eka Fitriana; Agus Saputra (Program Studi Pendidikan Bahasa Inggris, 2026)
Motivation plays a central role in determining students’ success in learning English, particularly in rural educational contexts where exposure to the language is limited. In many rural senior high schools in Indonesia, students demonstrate fluctuating levels of engagement due to limited facilities, minimal communicative practice, and restricted access to authentic English input. Despite the importance of motivation in second language acquisition, qualitative investigations focusing on rural senior high school contexts remain limited. Therefore, this study aimed to identify internal and external factors influencing students’ motivation and to examine instrumental and integrative motivational orientations among students at SMAN 1 Batukliang Utara. This research employed a qualitative case study design grounded in Gardner’s (1985) socio-educational model and Dörnyei’s (1998) motivational framework. The participants consisted of ten eleventh-grade students and two English teachers selected through purposive sampling. Data were collected through semi-structured interviews, classroom observations, and document analysis. The data were analyzed thematically following Braun and Clarke’s framework, using both deductive and inductive coding procedures. The findings indicate that internal motivation exists but is strongly influenced by students’ self-confidence and anxiety levels. External factors, particularly teacher encouragement, peer dynamics, and classroom atmosphere, significantly affect students’ engagement. Instrumental motivation is dominant, as students primarily associate English learning with academic achievement and career opportunities. Meanwhile, integrative motivation is present but remains underdeveloped and requires systematic reinforcement. The study concludes that students’ motivation is multidimensional and context-dependent, emphasizing the importance of balanced motivational development in rural EFL settings.